2013
DOI: 10.1007/s00415-013-7189-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased gait variability is associated with the history of falls in patients with cerebellar ataxia

Abstract: Falls are common in patients with cerebellar ataxia (CA). Identification of gait variables associated with a higher risk of falls allows us to detect fallers and initiate protective procedures early. Gait variability, which is increased in CA patients, is a good predictor of falls in elderly subjects and patients with neurodegenerative diseases. The relationship between gait variability and fall risk in patients with different cerebellar disorders was systematically investigated. A total of 48 patients with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 47 publications
5
74
0
3
Order By: Relevance
“…The authors reported that gait variability was significantly higher in the FA group compared with healthy subjects. Another study reported a significant relationship between gait variability and fall risk, particularly with slow walking, in people with a variety of cerebellar disorders [27]. The results are comparable to our findings of a significant correlation between stride length variability during both comfortable and fast walking and balance as assessed using the BBS and the LOS test.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The authors reported that gait variability was significantly higher in the FA group compared with healthy subjects. Another study reported a significant relationship between gait variability and fall risk, particularly with slow walking, in people with a variety of cerebellar disorders [27]. The results are comparable to our findings of a significant correlation between stride length variability during both comfortable and fast walking and balance as assessed using the BBS and the LOS test.…”
Section: Discussionsupporting
confidence: 93%
“…Gait variability is well documented in people with cerebellar ataxia and is related to walking impairment [6,7], gait speed [26] and falls [27]. Subjects with a variety of cerebellar ataxias exhibited significant variability in step and stride length, cadence, step time and stance time [6].…”
Section: Discussionmentioning
confidence: 99%
“…As a main finding, cerebellar ataxic gait disorder did not compromise the measurement accuracy estimated by betweenmethod comparison and measurement precision estimated from repeated testing. Increased spatiotemporal variability of stepping movements as the most consistently reported finding in ataxia [2,3] was also shown in our SCA14 cohort. However, measures of gait variability showed lowest consistency between methods in CTR as well as low agreement in retest in both groups.…”
Section: Discussionsupporting
confidence: 65%
“…It is characterized by a broad-based and more variable stepping as the most consistent finding that results in slowness of gait and falls [1][2][3]. The clinical assessment of walking ability forms part of commonly used rating scales for this disorder [4].…”
Section: Introductionmentioning
confidence: 99%
“…Gait variability is a well-established risk factor for falls in elderly subjects and patients with neurodegenerative diseases [4]. In persons with COPD, lower limb muscle weakness and impaired activities of daily living predict falls, though little was known on the influence of gait deficits [5].…”
Section: From the Authorsmentioning
confidence: 99%